THE ANALYSIS OF THE IMPACT OF HALAL LITERACY AND HALAL AND HALAL CERTIFICATION COSTS ON INTEREST IN CONDUCTING HALAL CERTIFICTION IN THE CULINARY MSME SECTOR - Sholikhah, Amaliatus; Alrasyid, Harun; Anwar, Siti Aminah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to analyze the influence of halal literacy and halal certification costs on the intention of culinary MSME actors in Malang City to pursue halal certification. Halal certification is an important factor in ensuring that products consumed by the Muslim community meet Islamic requirements while also enhancing business competitiveness. However, low levels of halal literacy and perceptions regarding certification costs remain major obstacles, particularly among MSMEs. This research adopts a quantitative approach using multiple linear regression to examine the relationship between halal literacy (X₁), halal certification costs (X₂), and the intention to obtain halal certification (Y). The sample consisted of 105 culinary MSME actors selected using purposive sampling. The results indicate that simultaneously, halal literacy and certification costs have a significant effect on business actors’ intention to pursue halal certification. Partially, both halal literacy and halal certification costs show a positive and significant influence on the intention to certify. These findings suggest that improving MSMEs’ understanding of the importance of halal products can encourage greater participation in the certification process. At the same time, perceptions regarding costs can be addressed through outreach and subsidy programs. This study provides strategic implications for government bodies and relevant institutions in formulating supportive policies that strengthen the national halal industry.